Polymorphisms in TSHR gene and the risk and prognosis of autoimmune thyroid disease in Tunisian population - Zaaber, I. (Acta Endocrinol (Buchar), 2020)
BACKGROUND: Autoimmune thyroid diseases (AITD) including Graves’ disease (GD) and Hashimoto’s thyroiditis (HT) are complex genetic diseases. TSHR is considered as candidate gene in GD. This finding prompted us to investigate the association of TSHR gene polymorphism with the risk and the prognosis of AITD in Tunisia. METHODS: A total of 84 healthy controls and 91 patients with AITD (69HT and 22 GD) were genotyped for TSHR rs74067403A>G polymorphism and 134 healthy controls and 149 patients with AITD (98 HT and 51 GD) were genotyped for TSHR rs1054708 T>C polymorphism. RESULTS: For rs1054708, we found an association between HT, AITD and the heterozygous genotype TC, the mutated genotype CC and the genotypes presented the mutated allele C (TC+CC) and with mutated allele C. The heterozygous genotype TC and the genotypes that presented the mutated allele C of rs1054708 are associated with male patients with AITD evenly the heterozygous genotype TC is associated with age of onset of disease. CONCLUSIONS: These preliminary results suggest that TSHR rs1054708 polymorphism may be a protective factor against HT and AITD. This polymorphism can affect the etiology of AITD between men and women and also by age.